2014
DOI: 10.2139/ssrn.2539013
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Effects of Childhood Conditions on Third Generation Health and Education Outcomes

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Phone: +49-621-181-1923; Fax: +49-228-73-9239. AbstractThis paper examines the extent to which pre-puberty nutritional conditions in one generation affect productivity-related outcomes in later generations. Recent findings from the biological literature suggest that the so-called slow growth period around age 9 is a sensitive period for male germ cell developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…In general, such outcomes have been marked by a changing prevalence over time. They have also been shown to be associated with ancestral exposures to toxins such as DDT pesticides [11], and stressors such as famine and war [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, such outcomes have been marked by a changing prevalence over time. They have also been shown to be associated with ancestral exposures to toxins such as DDT pesticides [11], and stressors such as famine and war [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the prevalence of spirituality/religiosity shows a dramatic change over time, in this paper we investigate whether there is any evidence indicating possible intragenetic or transgenetic associations involving either exposures to cigarette smoking or traumatic events in previous generations. Since other studies have shown the pre-pubertal ages to be of particular importance [e.g., 13,14], we have ensured that such apparently susceptible ages of the grandparents at exposure are considered in the analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Studying paternal mechanisms in human populations requires disentangling socioeconomic, biological, and psychological or cultural effects and maternal and paternal stressors. Research thus has focused on the third generation, but sample sizes are small ( 20 , 25 , 26 ) or lifespans incomplete ( 27 ). We have complete lifespans and detailed information on the socioeconomic and family structure for 4,593 children of 1,407 former POWs and 15,310 children of 4,960 non-POW veterans.…”
mentioning
confidence: 99%
“…Studies of the effects of historical events such as the Dutch Hunger Winter 1944–45 or the Chinese Great Leap Forward Famine 1959–61 on physical and mental health have shown an association between prenatal famine and adult body size, diabetes mellitus, and schizophrenia (Lumey et al ., 2011). There are also indications (including studies on historical data from Överkalix in northern Sweden) that these effects may be epigenetically transferred across generations (Kaati et al ., 2007; van den Berg and Pinger, 2016). Early malnutrition, as well as other early-life adversities, can induce long-term alterations in the metabolic and neuroendocrine systems that increase vulnerability to stress and obesity risk throughout life (Sawaya et al ., 2004; Yam et al ., 2015); such mechanisms could in theory also be involved in the development of eating disorders.…”
Section: Discussionmentioning
confidence: 99%